Prevalence of Hepatitis D Virus Co-Infection among HBsAg-Positive Patients in Abakaliki Metropolis, Ebonyi State, Nigeria - Azibanyam, Okosigha Saviour; Kenneth, Imarenezor Edobor Peter; Vivian, Anyiam Ifeoma (Darul Yasin Al Sys, 2025)
Hepatitis delta virus (HDV) is a defective RNA virus that requires co-infection with Hepatitis B virus (HBV) for replication and expression. This study aimed to determine the prevalence of HDV co-infection among HBsAg-positive patients in Abakaliki Metropolis, Ebonyi State, Nigeria. A cross-sectional analytical design was employed, involving 1,000 patients who presented at the Federal Teaching Hospital Abakaliki (FETHA) and Mile 4 Hospital Ishieke during the study period. Screening for HBV infection was conducted using the Skytec one-step rapid diagnostic kit, identifying 89 (8.9%) HBsAg-positive individuals. Subsequently, anti-HDV IgM serology testing was performed using ELISA on serum samples from HBsAg-positive patients to detect HDV co-infection. HDV IgM antibodies were detected in 5 (5.6%) of the HBsAg-positive patients—four pregnant women and one blood donor. Age-specific HBsAg prevalence was highest in the 24–28-year age group (13.5%), followed by 19–23 years (9.4%) and 29–33 years (4.0%). Married individuals exhibited a higher prevalence (16.6%) than singles (4.8%). Educational level was also associated with prevalence, with tertiary education holders showing the highest rate (20.0%) compared to those with primary education (4.8%). Based on occupation, the highest HBsAg prevalence was recorded among housewives (25.0%), followed by traders (14.7%), students (9.4%), and civil servants (4.3%). The presence of HDV co-infection highlights its potential to exacerbate the clinical course of HBV infection. The study recommends routine HDV screening among HBsAg-positive patients for early detection and clinical management. Additionally, public health interventions should include RNA-based diagnostic tools, increased awareness of HBV/HDV risks in high-risk populations, and integrated care strategies tailored to region-specific epidemiological patterns in Nigeria.